(untitled) (Research, Society and Development, 2021)
Objectives: To describe man’s perception of the importance of the media for his health and to discuss the impact of the media as a tool in the promotion of man’s health aimed at self-care. Methodology: Descriptive and exploratory study, with a qualitative approach, developed with 27 men from 18 years old, duly enrolled in a public university, located in the municipality of Rio de Janeiro. The data collection instrument was the semi-structured interview and, for data analysis, the content analysis technique was applied, according to the stages: pre-analysis, exploration of the material and treatment of the results, inference and interpretation. Results and Discussion: The study showed the perception of men about the means of communication and information for their health and the invisibility of health promotion actions on the male population in digital media. The analysis pointed out that the men in the study do not perceive themselves as contemplated by the media, regarding the health theme, and observe campaigns aimed at the female and child population, with the exception of “Novembro Azul” as a campaign dedicated to the male population. They also understand the importance of the media as a tool for stimulating, clarifying and reflecting on issues involving male issues in relation to health and self-care. Final considerations: In view of the invisibility of health promotion actions on the male population in digital media, easy-to-understand campaigns are needed, with an understanding of integrality in health, from a gender perspective.